Peluang Dan Tantangan Pengembangan Wisata Yoga Sebagai Produk Pariwisata Spiritual - I Putu Sagita Jaya Utama; I Made Arsa Wiguna (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2020)
Indonesian tourism has experienced rapid development in recent decades. This is shown by the increase in the Tourism Competitiveness Index in 2019. Indonesia, which was originally ranked 42, now rises to position 40 of 140 countries in the world. At the Southeast Asian level, Indonesia even ranked fourth. The success of this achievement is certainly due to the efforts of exploration, development and diversification of all potential attractions, ease of accessibility, number of facilities and strengthening of tourism institutions in each region. In line with the development of tourism, yoga activities in Bali have started to get the attention of the community, but these tourism activities still face several challenges, especially in developing potential attractions and human resources, especially in terms of management. In fact, yoga tourism has the potential for positive benefits if it is developed as an alternative to spiritual tourism as a result of the saturation of the concept of tourism development with a pattern of mass tourism.